In-situ Non-destructive Studies on Biofouling Processes in Reverse Osmosis Membrane Systems - Farhat, Nadia (2016)
Reverse osmosis (RO) and nanofiltration (NF) membrane systems are high-pressure membrane filtration processes that can produce high quality drinking water. Biofouling, biofilm formation that exceeds a certain threshold, is a major problem in spiral wound RO and NF membrane systems resulting in a decline in membrane performance, produced water quality, and quantity. In practice, detection of biofouling is typically done indirectly through measurements of performance decline. Existing direct biofouling detection methods are mainly destructive, such as membrane autopsies, where biofilm samples can be contaminated, damaged and resulting in biofilm structural changes. The objective of this study was to test whether transparent luminescent planar oxygen sensing optodes, in combination with a simple imaging system, can be used for in-situ, non-destructive biofouling characterization. Aspects of the study were early detection of biofouling, biofilm spatial patterning in spacer filled channels, and the effect of feed cross-flow velocity, and feed flow temperature. Oxygen sensing optode imaging was found suitable for studying biofilm processes and gave detailed spatial and quantitative biofilm development information enabling better understanding of the biofouling development process. The outcome of this study attests the importance of in-situ, non-destructive imaging in acquiring detailed knowledge on biofilm development in membrane systems contributing to the development of effective biofouling control strategies.